Unconventional band splitting of CeSb in the devil’s staircase transition - Tongrui Li; Zhanfeng Liu; Peng Li; Yuzhe Wang; Zhisheng Zhao; Shiwu Su; Zhicheng Jiang; Yuhao Hong; Hui Tian; Xin Zheng; Yi Liu; Yilin Wang; et al. (Communications Materials)
Abstract The interplay between magnetism and electronic band structure is a central theme in condensed matter physics. CeSb, with its complex devil’s staircase antiferromagnetic transition, offers a unique opportunity to explore this interplay. Using angle-resolved photoemission spectroscopy (ARPES), we investigate the electronic structure evolution across the devil’s staircase transition. Upon entering the antiferromagnetic phase, we observe an intriguing band splitting of the electron pocket around the X point. The energy separation between the split bands changes abruptly with temperature, consistent with the characteristics of the first-order phase transition. However, their respective spectral weights behave gradually with temperature. Combined with our density functional theory (DFT) calculations, we suggest that this atypical behavior deviates from conventional magnetically induced band splitting and potentially arises from the intricate modulation of paramagnetic and antiferromagnetic layers within the devil’s staircase transition. Our results provide insights into the complex relationship between electronic structure and magnetism in correlated electron systems.